Smart Home Control for Disabled Using Brain Computer Interface - Qin, Li Yi; Mohamed Nasir, Noorhamizah; Huq, M. Saiful; Ibrahim, B. S. K. K.; Narudin, Siti Khadijah; Alias, N. Akmal; Ab Ghani, Muhamad Amin (International Journal of Integrated Engineering, 2020)
Electroencephalography (EEG) based smart home control system is one of the major applications of Brain Computer Interface (BCI) that allows disabled people to maximize their capabilities at home. A Brain Computer Interface (BCI) is a device that enables severely disabled people to communicate and interact with their environments using their brain waves. In this project, the scope includes Graphical User Interface (GUI) acts as a control and monitoring system for home appliances which using BCI as an input. Hence, NeuroSky MindWave headset is used to detect EEG signal from brain. Furthermore, a prototype model is developed using Raspberry Pi 3 Model B+, 4 channels 5V relay module, light bulb and fan. The raw data signal from brain wave is being extracted to operate the home appliances. Besides, the results agree well with the command signal used during the experiment. Lastly, the developed system can be easily implemented in smart homes and has high potential to be used in smart automation.